POTENTIAL OF Rhizobium sp. I 3 AND Agrobacterium sp. I 3 7 IN FORMATION OF ROOT NODULES AND STIMULATING GROWTH OF Arachis hypogaea L. - Rosariastuti,Retno (2022)
ABSTRACT Rhizobium sp.I 3 and Agrobacterium sp.I 37 bacteria can increase plant growth and have the potential to become a member of the plant growth-promoting rhizobacteria (PGPR). Rhizobium bacteria can increase nitrogen availability for legume plants by forming nodules. Rhizobium sp. and Agrobacterium sp. are closely related; therefore, we speculated that Agrobacterium sp. can also form nodules. The study was based on completely randomized design and conducted from July 2019 to December 2019 in laboratories of the Faculty of Agriculture, Universitas Sebelas Maret, Central Java, Indonesia. The study included 11 different treatments of biofertilizer: P0, P1, P2, P3, P4, P5, P6, P7, P8, P9, P10, and P11 with each treatment in triplicate to obtain 36 experimental units. The results showed that the control treatment (P0) had 0 nodules, 8.26 g biomass, and 3.54% tissue nitrogen uptake. The three best treatments were in the order: P4 ( Rhizobium biofertilizer) with 174.3 root nodules, 14.77% tissue nitrogen (four times higher than that of control), and 24.05 g biomass; P8 ( Rhizobium biofertilizer) with 167 nodules, 12.42% tissue nitrogen (three times higher than that of control), and 19.26 g biomass; P5 ( Agrobacterium biofertilizer) with 146.6 root nodules, 13.15% tissue nitrogen (three times higher than that of control), and 16 g biomass.